(untitled) (Theatrum historiae, 2012)
The study deals with Count F. A. Sporck’s stay in Vienna and surrounding towns in the spring and summer 1727. On the grounds of investigations into his personal correspondence and a newly found calendar containing daily records taken by Sporck’s Hofmeister T. A. Seeman, the author attempts to explore Sporck’s opinions of the court, why he returned to Vienna after a long time, whether he suffered from social isolation at the court or who supported him in Vienna. At the same time the study deals with strategies employed by Sporck in order to win the favour of influential courtiers and seeks to answer the question whether he succeeded in this effort or was considered a weirdo.